Evangelism to the Tugutil Ethnic in Halmahera, North Maluku through the Implementation of Contextual Theological Models - Mawikere, Marde Christian Stenly; Hura, Sudiria; Wagiu, Meily Meiny; Ole, Fitria Fransisca (Tumou Tou, 2023)
This article describes the implementation of contextual theology models as transculturation contextualization of the evangelism to the Tugutil ethnic in Halmahera, North Maluku. The research was carried out using a qualitative ethnographic type approach built by literature studies on elements in local theology which include the inculturation of belief in God, man, sin and salvation. The purpose of this research is to formulate models of contextual theology that are relevant to the Tugutil ethnicity by utilizing their local theology. The results of this study show that there are elements of local theology of the Tugutil people who are "relatively close" so that they can be “meted” with the teachings of the Bible through functional substitute or re-culturation. In addition, there are also elements that are "relatively distant" from the teachings of the Bible, so they must experience worldview substitute or de-culturation. The final results of this study show that by examining, identifying and analyzing elements of local theology adhered to by the Tugutil ethnicity, it is possible to find similarities (potentials and opportunities) as well as differences (crises) between the teachings of the Bible and their animist-dynamism beliefs. This makes it possible to carry out a contextual evangelistic approach by implementing certain contextual theological models as transculturation.